2018
DOI: 10.1175/jcli-d-17-0899.1
|View full text |Cite
|
Sign up to set email alerts
|

CMIP5 Projected Change in Northern Hemisphere Winter Cyclones with Associated Extreme Winds

Abstract: In this study, 19 simulations from phase 5 of the Coupled Model Intercomparison Project (CMIP5) have been analyzed to examine how winter cyclones producing extreme near-surface winds are projected to change. Extreme wind thresholds correspond to a top 5 or top 1 cyclone per winter month in the entire Northern Hemisphere (NH). The results show that CMIP5 models project a significant decrease in the number of such cyclones, with a 19-model mean decrease of about 17% for the entire NH toward the end of the twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…S5), emphasizing the dominant influence of wind-wave modelling approaches. A detailed discussion on the dissimilarities between simulations is provided in Supplementary Information, supported by global pairwise comparisons of mean and variability bias in a coherent subset with common forcing-method (Supplementary Table 3 well-documented large-scale atmospheric wind circulation changes 36,37 and modes of natural climate variability 10 .…”
Section: Details Of Each Contribution and Respective Acronyms Are Promentioning
confidence: 99%
“…S5), emphasizing the dominant influence of wind-wave modelling approaches. A detailed discussion on the dissimilarities between simulations is provided in Supplementary Information, supported by global pairwise comparisons of mean and variability bias in a coherent subset with common forcing-method (Supplementary Table 3 well-documented large-scale atmospheric wind circulation changes 36,37 and modes of natural climate variability 10 .…”
Section: Details Of Each Contribution and Respective Acronyms Are Promentioning
confidence: 99%
“…Commonly only the most extreme cyclones in the top 10% of the intensity distribution are examined as these often provide the clearest climate change signal (Catto et al, 2010;Sinclair et al, 2020;Chang, 2018Chang, , 2017Zappa et al, 2013) and are associated with the highest impacts (Ulbrich et al, 2001, e.g.). However, it has been demonstrated in numerous studies that cyclones in the middle of the distribution can respond differently to the most extreme cyclones (Champion et al, 2011;Pfahl et al, 2015;Michaelis et al, 2017;Sinclair et al, 2020).…”
mentioning
confidence: 99%
“…However, Colle et al (2013) found the best (highest resolution) Coupled Model Intercomparison Project (CMIP5) models projected a 5-10% increase in cyclones and 5%-40% increase in deeper cyclones (<980 hPa) by the late twenty-first century inland along the U.S. east coast, but a 15%-20% decrease in cyclones and little increase in strong cyclones over the east coast water domain. Zappa et al (2013), Chang (2014Chang ( , 2018, and Seiler and Zwiers (2016) found similar decreases in extratropical cyclone frequency in various locations within the Pacific and Atlantic basins.…”
mentioning
confidence: 67%